Identification of 4 novel mutations of androgen receptor gene in 8 Chinese families with complete androgen insensitivity syndrome. Issue 2 (25th April 2018) - Wu, Q.; Wang, C.; Shi, H.; Mei, S.; Liu, L.; Xin, Y.; Kong, X.
Abstract :